Evaluation of the Psychometric Properties of the Mental Vulnerability Questionnaire in Undergraduate Students - Sequeira, Carlos (2019)
PURPOSE Translate, adapt the language, and assess the psychometric properties of the Mental Vulnerability Questionnaire (MVQ) in a Portuguese population sample of young adults. DESIGN AND METHODS A psychometric validation study was performed. The sample comprised 166 undergraduate students. Factor analysis was applied to extract three indicators. FINDINGS The MVQ showed divergent validity with the Positive Mental Health Questionnaire (p < .001) and convergent validity with the Mental Health Inventory including five items (p < .001). Reliability was verified through the assessment of internal consistency, evidencing positive outcomes (Cronbach's α = 0.81). PRACTICE IMPLICATIONS The MVQ shows psychometric properties enabling its adaptation to clinical practice and research, essential to an effective screening of mental vulnerability.